Intake and digestibility of lamb fed diets containing banana crop residues - do Carmo, Tânia Dayana; Barbosa, Paula Miranda; Geraseev, Luciana Castro; Costa, Diego Santana; Seles, Geziana Moreira; Duarte, Eduardo Robson (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effects of the inclusion of banana leaf or pseudostem hay in complete diets on the intake, nutrient digestibility, and ruminal short-chain fatty acid production by lambs. A total of 30 Santa Inês x Dorper lambs were allocated to five treatments: 400 g kg-1 Cynodon spp. hay; 200 g kg-1 banana leaf hay + 200 g kg-1 Cynodon spp. hay; 400 g kg-1 banana leaf hay; and 200 g kg-1 banana pseudostem hay + 200 g kg-1 Cynodon spp. hay and 400 g kg-1 banana pseudostem hay. The inclusion of banana crop residues had no effect on dry matter intake, organic matter, crude protein, neutral detergent fiber (NDF), acid detergent fiber, non-fiber carbohydrates, and total carbohydrates, which presented averages of 1,086.8, 1,000.1, 182.7, 374.3, 194.7, 390.2, and 771.6 g per day, respectively. There was a reduction in NDF digestibility with the inclusion of 400 g kg-1 leaf hay, but no differences were observed in the other treatments. The addition of both banana leaf and pseudostem hay can replace Cynodon spp. hay without affecting intake, nutrient digestibility, and ruminal concentration of short-chain fatty acids.